Effectiveness of Islamic Monetary Instruments in Controlling Inflation: Evidence from Indonesia's Experience: Efektivitas Instrumen Moneter Syariah dalam Pengendalian Inflasi: Bukti Empiris Komprehensif dari Indonesia - Riri Aprilia Nur Afifah (Yayasan Cerdas Pedia Indonesia, 2025)
This study examines the effectiveness of Islamic monetary instruments in controlling inflation within Indonesia’s dual monetary framework. Utilizing monthly data from January 2017 to December 2022, a Vector Error Correction Model (VECM) is estimated to capture both short- and long-run dynamics between Consumer Price Index inflation and three core Shariah instruments: the Shariah Bank Indonesia Certificate (SBIS), the Shariah Deposit Facility (FASBIS), and the Islamic Interbank Money Market rate (PUAS). Unit root and Johansen cointegration tests confirm all series are I(1) and cointegrated, validating the VECM approach. Long-run coefficients reveal that FASBIS and PUAS exert significant negative impacts on inflation, whereas SBIS exhibits a counterintuitive positive association. Impulse Response Functions and Forecast Error Variance Decomposition further demonstrate that PUAS contributes most to inflation variance, followed by FASBIS, with SBIS contributing minimally. The findings suggest that liquidity-focused instruments (FASBIS and PUAS) are more reliable for inflation control, while SBIS’s structural limitations hinder its effectiveness. Policy implications include shifting emphasis towards interbank liquidity management and strengthening transmission channels for Shariah monetary policy.